Construction of ball-flower like NiS2@MoS2 composite for high performance supercapacitors. (10th January 2020) - Hou, Shuangyue; Lian, Yue; Xu, Zongying; Wang, Dawei; Ban, Chaolei; Zhao, Jing; Zhang, Huaihao
Abstract: the ball-flower like composite (NiS2 @MoS2 ) was successfully synthesized by a convenient two-step hydrothermal method using Ni(NO3 )2 ·6H2 O and (NH4 )6 Mo7 O24 ·4H2 O as precursors. MoS2 nano-sheets, uniformly generated on NiS2 surface, increases the surface roughness and porosity, and accelerates the electrons and ions transfer of the composite. The synergistic effect of Mo and Ni improves the conductivity of the materials. Furthermore, by controlling the atomic ratio of Mo to Ni in precursors, the composite MN-1 (the molar ratio of MoS2 to NiS2 is 1:1) with the best capacity performance was obtained. The morphology and composition were characterized by a variety of means, such as TEM, SEM, XPS, XRD, BET and EDX. The electrochemical measurement results exhibited high specific capacity (848.2 C g −1 at specific current of 1 A g −1 ) and good cycling stability (83.1% specific capacity retention after 10000 GCD cycles) of MN-1 in 6 M KOH. Furthermore, an asymmetric supercapacitor was assembled with MN-1 as positive electrode and activated carbon as negative electrode. When the power density is 0.8 kW kg −1, its energy density reaches up to 37.2 Wh kg −1 . The present work may offer new design strategy for electrode materials. Graphical abstract: The ball-flower like composite (NiS2 @MoS2 ) was successfully synthesized by a convenient two-step hydrothermal method. The MN-1 exhibits the best capacity performance. Image 1 Highlights: The ball-flower like composite (NiS2 @MoS2 ) was successfully synthesized by a convenient two-step hydrothermal method. MN-1 achieves the maximum specific capacity of 848.2 C g −1 at 1 A g −1 . MN-1 exhibits an excellent cycling stability (83.1% for 10000 cycles). The MN-1//AC delivers high energy density of 37.2 Wh kg −1 at a power density of 0.8 kW kg −1 .